Principal's Supervision Management to Enhance Teacher Pedagogical Competence: A Case Study at SMK Muhammadiyah 1 Moyudan: Manajemen Supervisi Kepala Sekolah untuk Meningkatkan Kompetensi Pedagogik Guru: Studi Kasus di SMK Muhammadiyah 1 Moyudan - Muflihun Ramadhan; Enung Hasanah; Dian Hidayati (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2025)
Purpose – This study aims to conduct an in-depth analysis of the principal's supervision management in enhancing the pedagogical competence of teachers at Sekolah Menengah Kejuruan (vocational high school) or SMK Muhammadiyah 1 Moyudan, focusing on four main stages: planning, organizing, implementation, and monitoring of supervision. Design/methods/approach – This study employed a qualitative approach with a case study design. The research was conducted from February to April 2025, with data collected through in-depth interviews with three informants: the principal, the vice-principal for curriculum affairs, and a teacher, as well as through documentation related to school supervision. Data validity was ensured through source triangulation, while analysis was performed using the Miles & Huberman model, which includes the stages of data collection, data reduction, data display, and conclusion drawing. Findings – The supervision management at SMK Muhammadiyah 1 Moyudan is conducted systematically through: (1) planning that emphasizes targets for pedagogical competence development, (2) fair and transparent organization among the supervision team, (3) communicative implementation supported by digital technology, such as WhatsApp for coaching and discussions, and (4) adaptive monitoring through routine evaluations and needs-based follow-ups for teachers. Supervision serves not only as a control mechanism but also as an effective tool for professional development that fosters improvements in teaching quality. Research implications/limitations – These findings can be adopted by other vocational high schools to strengthen teacher pedagogical competence by enhancing two-way communication, utilizing digital technology, and providing continuous coaching. This study is limited to a single school with a small number of informants; therefore, the generalization of its findings should be approached with caution. Originality/value – This research offers an empirical framework for the implementation of principal supervision in a vocational high school setting by integrating digital media into the teacher coaching process. This approach enriches the literature on educational supervision in Indonesia, particularly within the context of vocational education, which demands rapid adaptation to technological advancements and industry needs. Abstrak Tujuan – Penelitian ini bertujuan mengkaji secara mendalam manajemen supervisi kepala sekolah dalam meningkatkan kompetensi pedagogik guru di SMK Muhammadiyah 1 Moyudan, dengan fokus pada empat tahap utama: perencanaan, pengorganisasian, pelaksanaan, dan pengawasan supervisi. Desain/metode/pendekatan – Studi ini menggunakan pendekatan kualitatif dengan desain studi kasus. Penelitian dilaksanakan pada Februari–April 2025, dengan data diperoleh melalui wawancara mendalam terhadap tiga narasumber: kepala sekolah, wakil kepala sekolah bidang kurikulum, dan seorang guru, serta dokumentasi terkait supervisi sekolah. Validitas data dijaga melalui triangulasi sumber, sedangkan analisis dilakukan dengan model Miles & Huberman yang mencakup tahap pengumpulan, reduksi, penyajian data, dan penarikan kesimpulan. Temuan – Manajemen supervisi di SMK Muhammadiyah 1 Moyudan berjalan sistematis melalui: (1) perencanaan yang menitikberatkan pada target pengembangan kompetensi pedagogik, (2) pengorganisasian yang adil dan transparan di antara tim supervisi, (3) pelaksanaan yang komunikatif dengan dukungan teknologi digital seperti WhatsApp untuk coaching dan diskusi, serta (4) pengawasan adaptif melalui evaluasi rutin dan tindak lanjut berbasis kebutuhan guru. Supervisi tidak hanya menjadi alat kontrol, tetapi juga sarana pembinaan profesional yang efektif dalam mendorong peningkatan kualitas pengajaran. Implikasi/batasan penelitian – Temuan ini dapat diadopsi oleh sekolah menengah kejuruan lain untuk memperkuat kompetensi pedagogik guru melalui penguatan komunikasi dua arah, pemanfaatan teknologi digital, dan pembinaan berkelanjutan. Penelitian ini terbatas pada satu sekolah dengan jumlah informan yang sedikit, sehingga generalisasi temuan perlu dilakukan dengan hati-hati. Keaslian/nilai – Penelitian ini menawarkan kerangka empiris implementasi supervisi kepala sekolah pada lingkungan SMK dengan mengintegrasikan media digital dalam proses pembinaan guru. Pendekatan ini memperkaya kajian supervisi pendidikan di Indonesia, khususnya pada konteks pendidikan vokasi yang menuntut adaptasi cepat terhadap perkembangan teknologi dan kebutuhan industri.